Галузева енциклопедія як важливий етап розвитку наукової дисципліни та її терміносистеми (на прикладі циклу праць із гірництва й геології "Гірнича енциклопедія") - Білецький, Володимир Стефанович; Гайко, Геннадій Іванович (My University, 2018)
На прикладі циклу праць "Гірнича енциклопедія" показано особливості розвитку окремих наукових дисциплін – гірництва, геології; передусім їх фахового термінологічного забезпечення. Стаття характеризує "Гірничу енциклопедію", її актуальність для технічної освіти в Україні, інтеграції загалом вітчизняної вищої освіти в європейський та світовий освітній простір.

The peculiarities of the development of some scientific disciplines (such as mining, geology), primarily the professional terminology system are shown on the example of the project The Mining Encyclopedia (ukr .: Hirnycha Entsyklopediia). The study describes The Mining Encyclopedia, its relevance for technical education in Ukraine, as well as for the integration of national higher education in the European and world educational space in general.
Subject specific encyclopedias as an important stage in the development of scientific disciplines and terminology systems (on example of The Mining Encyclopedia as a work in mining industry and geology)
Keywords: галузеві енцикопедії; технічна термінологія; технічна освіта; геологічна освіта; subject specific encyclopedias; The Mining Encyclopedia; technical terminology; technical education